Health utilities in Chinese patients with coronary heart disease and impaired glucose tolerance (ACE): a longitudinal analysis of a randomized, double-blind, placebo-controlled trial - Leal, J; Becker, F; Lim, L-L; Holman, RR; Gray, AM (Wiley, 2022)
Background We estimate health-related quality of life and the impact of four cardiovascular events (myocardial infarction [MI], stroke, congestive heart failure, angina) and gastrointestinal events in 6522 Chinese patients with coronary heart disease (CHD) and impaired glucose tolerance (IGT) participating in the Acarbose Cardiovascular Evaluation (ACE) trial. Methods Health-related quality of life was captured using the EuroQol-5 Dimension-3 Level (EQ-5D-3L), with data collected at baseline and throughout the trial. Multilevel mixed-effects linear regression with random effects estimated health-related quality of life over time, capturing variation between hospital sites and individuals, and a fixed-effects linear model estimated the impact of cardiovascular and gastrointestinal events. Results Patients were followed for a median of 5 years (interquartile range 3.4-6.0). The average baseline EQ-5D score of 0.930 (SD 0.104) remained relatively unchanged over the trial period with no evidence of statistically significant differences in EQ-5D score between randomized treatment groups. The largest decrement in the year of an event was estimated for stroke (−0.107, P < .001), followed by heart failure (−0.039, P = .022), MI (−0.021, P = .047), angina (−0.012, P = .047), and gastrointestinal events (−0.005, P = .430). MI and stroke reduced health-related quality of life beyond the year in which the event occurred (−0.031, P = .006, and −0.067, P < .001, respectively). Conclusions Acarbose treatment had no impact on health-related quality of life in ACE trial participants with CHD and IGT. Events such as MI, stroke, heart failure, and angina reduce health-related quality of life around the time they occurred, but only MI and stroke impacted on longer-term health-related quality of life.